The impact of paterns protection on the price of pharmaceutical drugs in Kuching - Suraya, Binti Bujang (Universiti Malaysia Sarawak, (UNIMAS), 2003)
This new global rules, introduced by World Trade Organization (WTO) although have an important role in stimulating investment and innovation; have raise the costs of medicines. This paper examines the impact of patent on medicines prices in Kuching